Soil pqqC-harboring bacterial community response to increasing aridity in semi-arid grassland ecosystems: Diversity, co-occurrence network, and assembly process - Zhang, Mei; Zhang, Ruixi; Song, Riquan; An, Xilong; Chu, Guixin; Jia, Hongtao (Frontiers in Microbiology, 2022)
Aridity is increasing in several regions because of global climate change, which strongly affects the soil microbial community. The soil pqqC-harbouring bacterial community plays a vital role in soil P cycling and P availability. However, the effect of smaller shifts in aridity on the pqqC community is largely unknown. Here, based on high-throughput sequencing, we investigated the response patterns of the diversity, cooccurrence networks, and assembly mechanisms of the soil pqqC communities along a natural aridity gradient in adjacent pairs of natural and disturbed grasslands in Inner Mongolia, China. The results showed that the α-diversity of the pqqC community first increased and then decreased with increasing aridity in the natural grassland, while it linearly increased as aridity increased in the disturbed grassland. The pqqC community dissimilarity significantly increased with increased aridity, exhibiting a steeper change rate in the disturbed grassland than in the natural grassland. Increased aridity altered the pqqC community composition, leading to increases in the relative abundance of Actinobacteria but decreases in Proteobacteria. The composition and structure of the pqqC community showed significant differences between natural and disturbed grasslands. Moreover, the network analysis revealed that aridity improved the interactions among pqqC taxa and promoted the interspecific competition of pqqC microorganisms. The pqqC community assembly was primarily governed by stochastic processes, and the relative contribution of stochastic processes increased with increasing aridity. Furthermore, disturbances could affect pqqC-harbouring bacterial interactions and assembly processes. Overall, our findings fill an important knowledge gap in our understanding of the influence of aridity on the diversity and assembly mechanism of the soil pqqC community in grassland ecosystems, and this work is thus conducive to predicting the pqqC community and its ecological services in response to future climate change.